“And then you go home having anger issues”: investigating Police-perpetrated domestic violence in South Africa - Lopes, Claudia (Department of Public Law, 2025)
As those entrusted with the duties of safety, security, care and protection, police officers play a significant role in responding to the crisis of domestic violence in South Africa. Paradoxically, they are capable of perpetrating the very crime they are sworn to prevent and equally capable of failing to hold those who do accountable. Police-perpetrated domestic violence (PPDV) is a globally prevalent yet largely understudied phenomenon, particularly in the South African context. Drawing on literature, police oversight monitoring reports, quantitative data and interviews with South African Police Service (SAPS) Station Commanders and Domestic Violence coordinators, this dissertation sheds light on this largely underexplored phenomenon providing a more contextualised understanding of PPDV in South Africa with a more selective focus on the Western Cape where its rates are disproportionally high. Research findings illustrate the complexity of PPDV, revealing an interplay of multiple influences and factors that contribute to its emergence and undermine state efforts to address it. Its findings emphasise the need for targeted reforms to take the issue of PPDV and the wellness of police officers in South Africa far more seriously than is currently the case.